Tafsir Ayat Hak Anak dan Relevansinya dengan Pendidikan Anak Usia Dini - Itah Miftahul Ulum (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2017)
AbstractThe purpose of this research is to know some verses of the Qur'an and the Hadith of the Prophet on the rights of the child and its relevance with the child's education so that it can bring up a concept of early childhood education.Research methods in this study are al-tafsir al-maudhu'i, which starts from the inventory of the verses of the Qur'an and the Prophet's hadith about the rights of the child. The understanding of the verses of the Qur'an and the hadith of the Prophet begins with the approach of interpretation of bi al-mantsur and al-qawaid al-'arabiyah, and tafsir bi al-mantsur dan al-qawaid al-‘arabiyah, and ilmu tanasub al-suwar wa al-ayat. Then, referring to the commentators 'interpretations and the hadith scholars' hadiths to be analyzed and synthesized. Furthermore, find relevance with the education of children, then designed into a concept of early childhood education.The results of this research, is the rights of the child according to the Islam consists of a good parent has rights, the right to life, the right to health, the right syi'ar Islam, the right intake of nutrition and rights in education. As for the relevance to the child's education, is concerned about the system of values, functions in upbringing, learning materials, and learning methodology. The usefulness of this study is that it contributes to positive about the concept of early childhood education, so that it can serve as a guide in educating children, so that they become children of the noble character and Salih, creating a family of sakinah, and foster a sense of compassion.Keywords: Rights of the children, Child education, Shalih Kids. AbstrakTujuan dari penelitian ini adalah untuk mengetahui ayat-ayat al-Qur’an dan hadits Nabi tentang hak-hak anak dan relevansinya dengan pendidikan anak, sehingga bisa melahirkan sebuah konsep pendidikan anak usia dini. Metodologi penelitian yang digunakan adalah al-tafsir al-maudhu’i, yang dimulai dari menginventarisir ayat al-Qur’an dan hadits Nabi tentang hak-hak anak. Pemahaman ayat al-Qur’an dan hadits Nabi tersebut, dimulai dengan pendekatan tafsir bi al-mantsur dan al-qawaid al-‘arabiyah, dan ilmu tanasub al-suwar wa al-ayat. Kemudian, merujuk tafsir para ahli tafsir dan syarh hadits para ahli hadits untuk dianalisis dan disintesis. Selanjutnya, dicarikan relevansinya dengan pendidikan anak, kemudian didesain menjadi sebuah konsep pendidikan anak usia dini. Hasil dari penelitian ini, adalah hak anak menurut Islam terdiri dari hak memiliki orangtua yang baik, hak hidup, hak kesehatan, hak syi’ar Islam, hak asupan bergizi, dan hak pendidikan. Adapun relevansinya dengan pendidikan anak, adalah menyangkut sistem nilai, fungsi pengasuhan, materi pembelajaran, dan metodologi pembelajaran.  Kegunaan dari penelitian ini, adalah memberikan kontribusi positif tentang konsep pendidikan anak usia dini, sehingga bisa dijadikan panduan dalam mendidik anak, agar menjadi anak yang shalih dan berakhlak mulia, menciptakan keluarga sakinah, dan menumbuhkan kasih sayang.Kata Kunci: Hak Anak, Pendidikan Anak, Anak Shalih.